Project Namahana - Teschner, John (Forge, 2022)
""An enthralling tale of disappearances, deaths, dark secrets, and corporate evil." -Douglas Preston, #1 bestselling co-author of the Agent Pendergast series Nothing stays hidden forever... Two men, unified by a string of disappearances and deaths, search for answers-and salvation-in the jungles of Kaua'i. Together, they must navigate the overlapping and complicated lines between a close-knit community and the hated, but economically-necessary corporate farms-and the decades old secrets that bind them. Project Namahana takes you from Midwestern, glass-walled, corporate offices over the Pacific and across the island of Kaua'i; from seemingly idyllic beaches and mountainous inland jungles to the face of Mount Namahana; all the while, exploring the question of how corporate executives could be responsible for evil things without, presumably, being evil themselves"--